(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study delves into the impact of Soret effects on the unsteady free convection flow of an incompressible viscous fluid through a highly porous medium, confined by an infinitely moving vertical plate. The analysis considers thermal radiation, chemical reaction, and heat source influences. The fluid is characterized as gray, absorptive, and emissive, while not exhibiting scattering. Radiative heat flux is described using the Rosseland approximation within the energy equation. The dimensionless governing equations are solved analytically employing a perturbation technique. Through the investigation, the influence of various governing parameters on velocity, temperature, concentration, skin-friction coefficient, Nusselt number, and Sherwood number is elucidated through figures and tables.